TARGETING FAILURES AND BIOMETRIC REFORM IN INDONESIA’S PROGRAM KELUARGA HARAPAN (PKH): A POLICY ANALYSIS OF THE CONDITIONAL CASH TRANSFER BENEFICIARY REGISTRATION SYSTEM - Briliani Putri Pijar Pratiwi (PT Wahana Global Education, 2026)
This paper examines beneficiary registration reform in Indonesia’s Program Keluarga Harapan (PKH), a conditional cash transfer program serving approximately 10 million households. The program suffers persistent targeting failures arising from inclusion and exclusion errors in the Integrated Social Welfare Data (DTKS) registry, with leakage rates estimated between 17% and 23 % of total expenditure. Using systematic literature review and a weighted multi-criteria decision framework, this study evaluates three policy alternatives: comprehensive biometric and digital registry reform, an integrated whole-of-government electronic social protection platform, and incremental status quo adjustment. Drawing on comparative evidence from Colombia, India, Pakistan, and the Philippines, the analysis finds that biometric digitalization of the DTKS offers the strongest combination of cost-effectiveness, equity impact, and long-term sustainability. The paper recommends a phased three-stage implementation strategy supported by cross-ministerial data governance reform and performance- based subnational accountability mechanisms.